Congenital neurosyphilis presenting as neonatal sepsis - Wedi Iskandar; Vidi Permatagalih; Aris Primadi; Uni Gamayani (Journal of Infection in Developing Countries)
Introduction: Congenital syphilis involves any organs with various symptoms, including neurological signs. Neurosyphilis is a severe syphilis complication that can develop at any stage of illness.